2021
DOI: 10.1007/s10824-021-09406-7
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for heritage conservation strategies: a choice modelling approach

Abstract: Studies aiming at valuing cultural and natural heritage projects are often focussed on one or only a few sites, whereas planning decisions concerning the allocation of public funds to heritage conservation deal with classes of heritage rather than single sites. In addition, such planning decisions are almost always concerned with non-monetary values that need to be incorporated into assessment procedures if the total value of alternative strategies is to be estimated. In this paper, we put forward and estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The willingness of people to pay is one of the most important theories used to reflect heritage values given by individuals in a community [30][31][32]. Throsby et al found a significant contribution by the four dimensions of cultural value-aesthetic value, historical value, social value, and architectural value-to the formation of conservation preferences and through the public's willingness to pay [33]. Heritage education is essential in order to create all these cultural values merely among the younger generations.…”
Section: Introductionmentioning
confidence: 99%
“…The willingness of people to pay is one of the most important theories used to reflect heritage values given by individuals in a community [30][31][32]. Throsby et al found a significant contribution by the four dimensions of cultural value-aesthetic value, historical value, social value, and architectural value-to the formation of conservation preferences and through the public's willingness to pay [33]. Heritage education is essential in order to create all these cultural values merely among the younger generations.…”
Section: Introductionmentioning
confidence: 99%
“…Throsby D., Zednik A., Araña J. E. interpret the city "historic core" as certain classes of cultural heritage, including the city historical buildings, monuments, sights, and others [7]. Consequently, economic calculations in relation to the city "historic core" and economic models associated with the restoration and development of the "historic core" are to be carried out not for individual buildings and objects, but for the class of cultural heritage, i.e., by means of cumulative impact on the city identity and the value system of its inhabitants [7].…”
Section: O Horbanmentioning
confidence: 99%
“…On the one hand, the class of the city "historic core" forms cultural capital. Therefore, the buildings and objects that are part of the "historic core" and are defi ned as capital assets, embody or bring cultural value in addition to the economic value that they pos-sess [7]. On the other hand, the economic value of the city "historic core" class, measured as a direct use value or willingness to pay for unused demand, is expressed in monetary terms, while the cultural value of the "historic core" class is multidimensional and does not have a single unit of account.…”
Section: O Horbanmentioning
confidence: 99%
See 2 more Smart Citations